Tau–amyloid interactions in the rTgTauEC model of early Alzheimer's disease suggest amyloid‐induced disruption of axonal projections and exacerbated axonal pathology. Issue 18 (28th October 2013) - Pooler, Amy M.; Polydoro, Manuela; Wegmann, Susanne K.; Pitstick, Rose; Kay, Kevin R.; Sanchez, Laura; Carlson, George A.; Gomez‐Isla, Teresa; Albers, Mark W.; Spires‐Jones, Tara L.; Hyman, Bradley T.
ABSTRACT Early observations of the patterns of neurofibrillary tangles and amyloid plaques in Alzheimer's disease suggested a hierarchical vulnerability of neurons for tangles, and a widespread nonspecific pattern of plaques that nonetheless seemed to correlate with the terminal zone of tangle‐bearing neurons in some instances. The first neurofibrillary cortical lesions in Alzheimer's disease occur in the entorhinal cortex, thereby disrupting the origin of the perforant pathway projection to the hippocampus, and amyloid deposits are often found in the molecular layer of the dentate gyrus, which is the terminal zone of the entorhinal cortex. We modeled these anatomical changes in a transgenic mouse model that overexpresses both P301L tau (uniquely in the medial entorhinal cortex) and mutant APP/PS1 (in a widespread distribution) to examine the anatomical consequences of early tangles, plaques, or the combination. We find that tau uniformly occupies the terminal zone of the perforant pathway in tau‐expressing mice. By contrast, the addition of amyloid deposits in this area leads to disruption of the perforant pathway terminal zone and apparent aberrant distribution of tau‐containing axons. Moreover, human P301L tau‐containing axons appear to increase the extent of dystrophic axons around plaques. Thus, the presence of amyloid deposits in the axonal terminal zone of pathological tau‐containing neurons profoundly impacts their normal connectivity. J. Comp. Neurol. 521:4236–4248, 2013. © 2013 Wiley Periodicals, Inc.